(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The Avocation and professionalism worked to establish a representative performance in which educational theater was defined as an art with its techniques, methods, and theatrical experiences through transitional stages towards modernity.Among these theatrical experiences, the role of educational theater has been enhanced, and start to represent performance of amateurs to build an integrated human personality that has the ability to build a society that can continue education and learning. The goal of the amateur is to achieve self-pleasure and broadcast it to the other in exchange for the professional who aspires to reach several material and artistic gains and to broadcast an intellectual and educational message. The amateur is linked to his vision and desires, as he is linked intellectually and physically with performance programs to provide the elements for his technical and artistic success, and between this contrast, theatrical work is transformed into an elaborate art, each of which has its advantages, dimensions and skills that were granted experience to achieve the requirements of focus in the performing art theatrical and capture intertwined ideas, dialogues, tendencies, and emotions, to communicate emotionally in a purposeful educational theater requires great effort in forming and building the backbone of the structure of society. Accordingly, the researcher sought to reveal the characteristics of amateur representation in educational theater. Therefore, the researcher divided the subject of his research into four chapters. The first chapter included the research problem, which was represented in (What are the characteristics of amateur performance in educational theater?) The first chapter also included the importance of the research, its goal and limits and ended with defining the terminology, and the second chapter included (theoretical framework)The first topic (references of amateur acting performance), and the second topic (the characteristics of amateur acting in educational theater), and the third chapter included the research sample, the research tool, the research and analysis method for a play (fairy reality), and the fourth chapter included the results of the analysis, conclusions, then the list of sources